Factors in the choice of volitional regulation strategies among university students - V.N. Shlyapnikov (Экспериментальная психология)
The article presents the results of a study of volitional regulation strategies in university students. The hypothesis was tested that the choice of strategy is determined by the nature of the tasks facing students related to self-organization of educational activities, as well as individual characteristics of students: volitional, motivational spheres, self-awareness and psychodynamic properties. To test the hypothesis, students of different levels of education studying in full-time and distance learning departments were compared using a single-factor analysis. A total of 698 people took part in the study. The multiple linear regression method was used to test the influence of individual characteristics. The following methods were used: "Action Control Scale", "Questionnaire for identifying the severity of self-control in the emotional sphere, activity and behavior", "Brief Academic Motivation Scale", PIL test, "General Self-Efficacy Scale", a modification of the Dembo-Rubinstein self-assessment technique, "Big Five Short Portrait Questionnaire (B5-10)". To assess the strategies of volitional self-regulation, students were offered a list of ways to solve problems that arise in the course of their studies, which they had to evaluate by the frequency of their use. Then, the students' answers were processed using factor analysis. As a result, six strategies were identified: "planning", "self-regulation", "self-compulsion", "additional classes", "seeking help", "detachment from the problem". It was shown that full-time and distance learning students differ significantly in five of the six strategies. Master's students more often resort to self-regulation, bachelor's students more often seek help, and specialist students more often resort to self-compulsion. It was also shown that the choice of strategies is significantly influenced by the characteristics of volitional regulation and academic motivation of students.